VLSI implementation of a new standard for lossless compression of continuous-tone still images - Aktürk, A. Suat. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1998., 1998)
In this thesis, an integrated circuit realizing lossless compression of continuous-tone still images is designed. Lossless compression has two main parts. In the encoding part, digital source image data are encoded in order to generate compressed image data. In the decoding part, this compressed image data are decompressed and digital reconstructed image data are obtained which must be identical to the digital source image data. First, the circuit was created by drawing its schematic diagram, then it was designed, optimized, simulated and its IC layout was created and prepared for IC processing by using the Mentor Graphics v.8.4.1 tools running on a Sun Sparc2 workstation. In the design, Europractice Alcatel Mietec 0.7 mm CMOS target technology is used. Then, by putting a select switch into the circuit, the mode of coding process, whether working as an encoder or decoder, can be chosen.
Keywords: Integrated circuits -- Very large scale integration.; Coding theory.; Image compression.